Kritik Terhadap Paham Liberalisasi Syariat Islam - Nirwan Syafrin (Universitas Darussalam Gontor, 2009)
The movement of liberalism in Islamic world at the time being has made the Islamic syari’ah as the object of criticism which must be banned because it considered as the problem of history. Strangely, they always proud on what they have done as interpretation and renovation. In Indonesia liberalism movement factually not without the chesing scenario of politics and world intellects. It is really difficult to avoid the influence of America and its campaign against terrorism in this movement. They try to raise a positive image then what has been presented by the groups of radicalism, fundamentalism, and conservatism, they seem like to change this image, but finally they changed their own image which tend to be more Westernised than the West itself. At least there are three categories, the argumentation of the liberalist against the enforcement of Islamic syariat, that is: historical argumentation, with consideration on Shariah purposes and human right. This article elaborates the position of liberalism view in contemporary Islamic thought, retrieves the process of liberalism in the view of Syari’ah modernisation and criticism toward argumentations of liberalists.